1976
DOI: 10.1002/aic.690220113
|View full text |Cite
|
Sign up to set email alerts
|

Secondary nucleation of two fast growth systems in a mixed suspension crystallizer: Magnesium sulfate and citric acid water systems

Abstract: MICHAEL E. PRUDlCHA solid/liquid separation process based on the transfer of hydrophobic coated mineral particles from a hydrocarbon to an aqueous phase is described. This process could be used, for example, to remove mineral matter from coal derived liquids in order to meet fuel specifications. A model system which involves hydrophobic, asphaltic, coated mineral matter particles in a model liquid, xylene, was used in conjunction with the mechanistic studies. The mineral matter distribution coefficient to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…This is probably true because more aragonite would be formed by nucleation at a higher temperature, as reported by Wray and Daniels (1957). Nevertheless, the temperature effects were observed for other systems without changing the crystal morphology, such as potassium alum (Wu et al, 1991;Rousseau and Woo, 1980) and citric acid (Sikdar and Randolph, 1976). Thus, the temperature might have dual effects on the growth of aragonite seeds.…”
Section: Temperature Effects In the Absence Of Magnetic Fieldmentioning
confidence: 79%
See 1 more Smart Citation
“…This is probably true because more aragonite would be formed by nucleation at a higher temperature, as reported by Wray and Daniels (1957). Nevertheless, the temperature effects were observed for other systems without changing the crystal morphology, such as potassium alum (Wu et al, 1991;Rousseau and Woo, 1980) and citric acid (Sikdar and Randolph, 1976). Thus, the temperature might have dual effects on the growth of aragonite seeds.…”
Section: Temperature Effects In the Absence Of Magnetic Fieldmentioning
confidence: 79%
“…Nevertheless, almost all of the clusters existing in the supersaturated solution were transformed into those available for aragonite growth under magnetizing for a long period of time. At higher temperatures, the clusters adsorbed on the crystal surface were more active in causing a higher surface-integration rate, just like the systems of potassium alum and citric acid (Sikdar and Randolph, 1976;Wu et al, 1991). For the case without the treatment of magnetic field, none of the clusters were available for aragonite growth at room temperature.…”
Section: Temperature Effects In the Presence Of Magnetic Fieldmentioning
confidence: 95%
“…Experimental results range from 1.8 to 7.82 and several studies report h=2-2.5 (Garside and Shah, 1980). However, Sikdar and Randolph (1976) found that the stirring rate did not effect the nucleation rate of citric acid and magnesium sulfate, and it has been reported (Mullin and Leci, 1972;Wang et al, 1981) that the influence of agitation on citric acid nucleation vanishes at increasing rotations per minute. A low order of dependence may reflect regeneration or survival limitation of the nucleation process.…”
Section: Crystallization Kinetics Of Succinic Acidmentioning
confidence: 89%
“…The on-line measurement of crystal growth and nucleation rates in a mixed suspension, mixed product removal (MSMPR) crystallizer has proved to be a versatile tool for studying nucleation/growth rate kinetics while directly observing the mechanisms underlying such kinetics (for example, Randolph and Cise, 1972;Sikdar and Randolph, 1976). Most previously studied systems are characterized by relatively high solubilities, low supersaturation, and the dominance of secondary nucleation.…”
Section: Scopementioning
confidence: 99%
“…The on-line sampling technique used previously in similar studies (Randolph and Cise, 1972;Sikdar and Randolph, 1976) was implemented in this study. However, the capability of on-line regression of semilog popu-Iation data to the theoretical MSMPR form was added utilizing the system shown schematically in Figure 2.…”
Section: Research Approachmentioning
confidence: 99%